Variabiliti harga relatif dan inflasi: Bukti empirikal di Semenanjung Malaysia, Sabah dan Sarawak - Abdul Karim, Zulkefly; Zaidi, Mohd Azlan Shah; Jusoh, Mansor (Universiti Utara Malaysia, 2008)
Purpose - The paper iinvestigate fhe relationship between relative price variability among groups of goods and inflation in Peninsular Malaysia, Sabah, and Sarawak. Design/Methodology/Approach - The study utilised the non-linear time series technique of Smooth Transition Auto-Regressive (STAR) models on monthly time series data from January 1970 to Mac 2005. Finding - Based on the empirical evidence,it was clearly shown that the relative price variability has a non-linear characteristic in the form of logistic STAR (LSTAR). In addition, inflation was also significant and positively related to influence the relative price variability in all three regions. The empirical findings also revealed that the relationship between the relative price variability and inflation is in non-linear form. The findings support the menu-cost theory which stipulated that the variability of price will increase when there is an increase in the general price level. Besides that,the stochastic component of the relative price variability had shown persistency in all regions. Originality/Value - The paper reveals the existence of a relationship between relative price variability and inflation in each of the three regions of Malaysia and suggests some policy implications on controlling inflation. Paper type -Research Paper